2016
DOI: 10.1063/1.4954122
|View full text |Cite
|
Sign up to set email alerts
|

Contrast-enhanced digital mammography and other techniques based on image subtraction

Abstract: A method to optimize the image acquisition protocol of a MicroCT unit for preclinical studies using contrast-enhanced digital subtraction AIP Conference Proceedings 1747, 080003 (2016) Abstract. This article reviews research done by the author and collaborators in the general area of subtraction techniques applied to radiological images, in particular in contrast-enhanced digital mammography (CEDM). Main achievements have been the development and phantom validation of a general formalism to subtract images usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…where RV being the resulting pixel value, E1V being the pixel values for the low-energy image, E2Vthe pixel values of the high-energy image and c is a coefficient, which depends on the attenuation coefficients of the background tissue for the low-and high-x-ray energy used [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…where RV being the resulting pixel value, E1V being the pixel values for the low-energy image, E2Vthe pixel values of the high-energy image and c is a coefficient, which depends on the attenuation coefficients of the background tissue for the low-and high-x-ray energy used [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Further, the authors reported iodine concentrations required for use of CEDEM with a clinical system turned to be higher than those required for use with a synchrotron source. Brandan [4] reviewed a series of investigations in the field of DES and SETS. The author reported both theoretical studies and such that are based on phantom experiments, which proved that SETS is superior to the DES technique.…”
Section: Introductionmentioning
confidence: 99%